Increasing digital maturity in innovative development management in a company - S. V. Sviridova; D. N. Horoshilov (Вестник университета)
Digital maturity level determines the ability of an enterprise to quickly and effectively implement digital management tools, including in innovative activities. Increasing digital maturity is becoming a necessary task for innovative and active enterprises aimed at increasing business sustainability. Studying theoretical and methodological aspects of enterprises’ digital maturity allowed us to identify a range of current issues. Theoretical substantiation of the concept and content of an enterprise’s digital maturity has been carried out, and its key characteristics have been formed. Digital maturity assessment stages and tasks of increasing digital maturity in managing an enterprise’s innovative development have been highlighted. Methodological approaches digital maturity assessment has made it possible to form an authors’ way of organizing and managing digital maturity level. The authors recommend to create a working group and a Coordinating council for managing an enterprise’s digital maturity. The functional content of the activities of the council and its specialists at different levels has been proposed. To solve the problem of determining the time spent on managing and monitoring digital maturity, a mathematical model for time redistribution for operations has been developed. The optimization of operations complexity redistribution in monitoring an enterprise’s digital maturity has been carried out. The article concludes that effective organizational and technological management of an enterprise will open up the possibility of increasing its digital maturity level.